Investigation of pulmonary infection pathogens in neurological intensive care unit - Fengying Quan; Guangwei Liu; Liang Wang; et al (Dove Medical Press, 2011)
Fengying Quan, Guangwei Liu, Liang Wang, Xuefeng WangDepartment of Neurology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, ChinaPurpose: The purpose of this study is to investigate the distribution and antimicrobial susceptibility of pathogenic bacteria in inpatients with pulmonary infection in the neurological intensive care unit (NICU).Methods: A total of 947 sputum specimens of 428 inpatients from May 2007 to May 2008 in the NICU were enrolled in the study, and bacterial identification and antibiotic susceptibility tests were analyzed using a VITEK 2 system.Results: A total of 400 positive bacterial strains were separated from 947 sputum specimens, with Gram-negative bacteria accounting for 69.0% of the total strains collected. The most common strain of Gram-negative bacteria was Klebsiella pneumoniae (20.5%). Gram-positive bacteria accounted for 10.0% of the total strains, with the most common strain being Staphylococcus aureus (2.5%). Fungal species accounted for 21.0% of the total strains, and the most common strain collected was Candida albicans (12.25%). Imipenem was the most effective antibiotic against Gram-positive and Gram-negative bacteria. The drug resistance rate of Gram-positive bacteria to penicillin G was 100%, and the Gram-positive bacteria were 100% sensitive to teicoplanin, vancomycin, and linezolid.Conclusions: Gram-negative bacterial infections account for the majority of pulmonary infections in the NICU, with fungal infections being the second most common infection type observed. In addition, fungal infections seem to be related to mortality in the NICU.Keywords: nosocomial infection, pulmonary infection, drug resistance, neurological intensive care unit